Statin uses in adults with non-dialysis advanced chronic kidney disease: Focus on clinical outcomes of infectious and cardiovascular diseases - Hsiao, Ching-Chung; Yeh, Jih-Kai; Li, Yan-Rong; Sun, Wei-Chiao; Fan, Pei-Yi; Yen, Chieh-Li; Chen, Jung-Sheng; Lin, Chihung; Chen, Kuan-Hsing (Frontiers in Pharmacology, 2022)
Background: Statins are commonly used for cardiovascular disease (CVD) prevention. Observational studies reported the effects on sepsis prevention and mortality improvement. Patients with chronic kidney disease (CKD) are at high risk for CVD and infectious diseases. Limited information is available for statin use in patients with non-dialysis CKD stage V. Method: The retrospective observational study included patients with non-dialysis CKD stage V, with either de novo statin use or none. Patients who were prior statin users and had prior cardiovascular events were excluded. The key outcomes were infection-related hospitalization, major adverse cardiovascular events (MACE) (non-fatal myocardial infarction, hospitalization for heart failure, or non-fatal stroke), and all-cause mortality. The data were retrieved from the Chang Gung Research Database (CGRD) from January 2001 to December 2019. Analyses were conducted with Cox proportional hazard regression models in the propensity score matching (PSM) cohort. Result: A total of 20,352 patients with CKD stage V were included (1,431 patients were defined as de novo statin users). After PSM, 1,318 statin users were compared with 1,318 statin non-users. The infection-related hospitalization (IRH) rate was 79.3 versus 94.3 per 1,000 person-years in statin users and statin non-users, respectively [hazard ratio (HR) 0.83, 95% confidence interval (CI) 0.74–0.93, p = 0.002]. The incidence of MACE was 38.9 versus 55.9 per 1,000 person-years in statin users and non-users, respectively (HR, 0.72; 95% CI 0.62–0.83, p < 0.001). The all-cause mortality did not differ between statin users and non-users, but statin users had lower infection-related mortality than non-users (HR, 0.59; 95% CI 0.38–0.92, p = 0.019). Conclusion:De novo use of statin in patients with non-dialysis CKD stage V reduced the incidence of cardiovascular events, hospitalization, and mortality for infectious disease. The study results reinforced the benefits of statin in a wide range of patients with renal impairment before maintenance dialysis.